Intraventricular Trigone Pleomorphic Xanthoastrocytoma: A Rare Presentation with Favorable Prognosis in a Young Adult—A Case Report - Chaisawasthomrong, Chonnawee (Asian Journal of Neurosurgery, 2025)
Pleomorphic xanthoastrocytoma (PXA) is a rare, Grade II astrocytic tumor typically found in the temporal lobe and often presents with seizures. We report a unique case of intraventricular trigone PXA, a rare location that mimicked an intraventricular meningioma on imaging. A 26-year-old male presented with progressive visual loss, and magnetic resonance imaging revealed a well-defined lesion in the right lateral ventricle. The patient underwent subtotal tumor resection, followed by adjuvant radiotherapy. Histopathological analysis confirmed PXA with BRAF V600E mutation, and subsequent imaging showed successful tumor control with no recurrence after 2 years. This case highlights the importance of differentiating PXA from other neoplasms, such as meningiomas, and demonstrates the favorable prognosis of PXA when appropriately managed.
Keywords: pleomorphic xanthoastrocytoma; intraventricular trigone; gliomas